Determination of Camel Hide Gelatin in Donkey Hide Gelatin Based on Enzymatic Digestion by Ultra-performance Liquid Chromatography-Tandem Mass Spectrometry - Qiangsheng Xie; Weijian Wang; Tianyang Gao; Feiyan Diao; Wenyue Hu; Xiaoyun Wu; Silong Li; Feng Shi; Liping Gong; Qiyan Li; Guangxi Zhai (Journal of Food Protection)
The commercial value and diversified applications of donkey hide gelatin (DHG) have precipitated sophisticated adulteration practices, particularly with camel-hide gelatin substitutes. We present a mass spectrometry-based strategy to authenticate species-specific collagen peptides in commercial DHG. A new qualitative and quantitative methodology is constructed for camel hide gelatin(CHG) material analysis in DHG. It consists of enzyme-mediated digestion, ultra-high-performance liquid chromatography (UHPLC), and triple quadrupole mass spectrometry (MS/MS) with multireaction monitoring (MRM) mode. In brief, the samples were digested with trypsin and subjected to efficient and quick separation by UHPLC, and MS/MS performed CHG identification and determination analysis. Two peptides (Camel peptide A, CPA, and Camel peptide B, CPB) were identified as CHG-specific peptides. A specificity test was then used to verify these two peptides. The method performance showed that these two peptides could distinguish CHG from other animal hide gelatins. The CPA and CPB detection limits were 5 μg/kg and 3 μg/kg, respectively. LC-MS/MS analysis detected CPA and CPB in 4.5% of market-collected DHG samples (n = 157), confirming the prevalence of this emerging adulteration practice. Thus, the present protocol is a sensitive, accurate, quick, and suitable application of species-specific peptide biomarkers, ensuring the quality of DHG products and making them authentic and traceable to protect consumers from potential health risks and food frauds.